Sociology of Ereignis: A New Ontological Foundation for Prophetic Social Science - Rifqi Khairul Anam (Jurnal Sosiologi Reflektif, 2025)
In Indonesia’s intellectual landscape, Kuntowijoyo’s Prophetic Social Science emerged as a critical response to the dominance of Western positivism, which has been criticized for its inability to grasp the ethical and transcendental dimensions of social reality. Despite its transformative vision, this framework has long faced a fundamental challenge: the absence of a coherent ontological foundation that could sustain its three pillars—humanization, liberation, and transcendence. This research aims to address that gap by proposing Heideggerian social ontology as a new philosophical basis for Prophetic Social Science. Using a qualitative method of critical conceptual analysis, this research examines key philosophical and sociological texts through a hermeneutic–phenomenological lens. The analysis proceeds through interpretive deconstruction and reflexive engagement to uncover the ontological and epistemological assumptions behind positivism and Heideggerian thought. The findings show that positivism’s ‘flat’ ontology cannot accommodate the prophetic vision, while Heideggerian social ontology provides a more authentic foundation for a Sociology of Ereignis—a framework that centers meaningful events, reflexivity, and disclosure. The implication of this research is that sociological inquiry, especially within Muslim societies, must be reoriented toward ontologically grounded and ethically engaged methodologies that take lived meaning and transcendence seriously. Dalam lanskap intelektual Indonesia, Ilmu Sosial Profetik Kuntowijoyo lahir sebagai respons kritis terhadap dominasi positivisme Barat yang sering dianggap gagal memahami dimensi etis dan transendental dari realitas sosial. Meskipun memiliki visi yang transformatif, kerangka ini menghadapi tantangan mendasar berupa ketiadaan landasan ontologis yang kokoh untuk menopang tiga pilarnya—humanisasi, liberasi, dan transendensi. Penelitian ini bertujuan untuk menjawab celah tersebut dengan mengusulkan ontologi sosial Heideggerian sebagai dasar filosofis baru bagi Ilmu Sosial Profetik. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis konseptual kritis, membaca teks-teks filsafat dan sosiologi utama melalui lensa hermeneutik-fenomenologis. Analisis dilakukan melalui proses dekonstruksi interpretatif dan refleksi kritis untuk menyingkap asumsi ontologis dan epistemologis di balik positivisme dan pemikiran Heidegger. Hasil penelitian menunjukkan bahwa ‘flat’ ontology dalam positivisme tidak mampu menampung visi profetik, sedangkan ontologi sosial Heideggerian menawarkan dasar yang lebih otentik bagi Sosiologi Ereignis—sebuah kerangka yang menempatkan peristiwa bermakna, refleksivitas, dan pengungkapan makna sebagai inti kajian. Implikasi penelitian ini adalah bahwa sosiologi, terutama dalam masyarakat Muslim, perlu diarahkan kembali pada metodologi yang berlandaskan ontologi dan komitmen etis, yang mampu menangkap makna dan dimensi transendensi secara lebih mendalam.